2023
DOI: 10.3390/ijms24031846
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background and Molecular Mechanisms of Juvenile Idiopathic Arthritis

Abstract: Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in the paediatric population. JIA comprises a heterogeneous group of disorders with different onset patterns and clinical presentations with the only element in common being chronic joint inflammation. This review sought to evaluate the most relevant and up-to-date evidence on current knowledge regarding the pathogenesis of JIA subtypes to provide a better understanding of these disorders. Despite significant improvements over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 127 publications
0
8
0
Order By: Relevance
“…Our findings on the pathomechanism of oligo JIA can not be generalized or extrapolated to the other subtypes of JIA. JIA subtypes show a variety of characteristics, biomarkers, and systemic features due to different pathophysiological mechanisms, caused by HLA genetic pre-disposition, effector cells and cytokines involved in the aetiopathogenesis [ 43 , 44 ]. We consider it a strength of our study that we focused exclusively on the persistent oligoarticular JIA, which is the least heterogeneous subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on the pathomechanism of oligo JIA can not be generalized or extrapolated to the other subtypes of JIA. JIA subtypes show a variety of characteristics, biomarkers, and systemic features due to different pathophysiological mechanisms, caused by HLA genetic pre-disposition, effector cells and cytokines involved in the aetiopathogenesis [ 43 , 44 ]. We consider it a strength of our study that we focused exclusively on the persistent oligoarticular JIA, which is the least heterogeneous subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CC can treat a variety of arthritis, and it is better for OA, RA and GA. CC has the characteristics of multiple components, multiple targets, and multiple pathways in the treatment of arthritis. Currently, IL-10, IL-1β, IL-6, MMP-3, TNF-α and other targets have been verified to play a role in treating arthritis by CC ( Table 2 ) ( Sun et al, 2011 ; Yuan et al, 2014 ; Kienhorst et al, 2015 ; Huang et al, 2019 ; Thomas, 2020 ; Che et al, 2021 ; Li et al, 2021 ; Wu et al, 2021 ; Arra et al, 2022 ; Zhang et al, 2022 ; Cao et al, 2022 ; Du et al, 2022 ; Pacifici, 2022 ; Wirth et al, 2022 ; Xiao et al, 2022 ; Yang et al, 2022 ; Sun et al, 2023a ; Barbarroja et al, 2023 ; Li et al, 2023 ; Brix et al, 2023 ; Wang et al, 2023b ; Wang et al, 2023 ; Ghosh et al, 2023 ; González-Chávez et al, 2023 ; Hecquet et al, 2023 ; Jahantigh et al, 2023 ; Ji et al, 2023 ; La Bella et al, 2023 ; Leung et al, 2023 ; Lin et al, 2023 ; Luo et al, 2023 ; Zeng et al, 2023 ; Zhang et al, 2023 ). However, the types of arthritis treated with these targets are not completely clear.…”
Section: Deep Exploration Based On Potential Therapeutic Targets For ...mentioning
confidence: 99%
“…Although the pathogenesis of JIA is extremely complex and the exact understanding is still unclear, dysregulation of the immune system including innate and adaptive immunity triggered by environmental and genetic factors is generally accepted 10–12. In the intricate realm of inflammatory responses, cytokines may play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of JIA is extremely complex and the exact understanding is still unclear, dysregulation of the immune system including innate and adaptive immunity triggered by environmental and genetic factors is generally accepted. 10–12 In the intricate realm of inflammatory responses, cytokines may play an important role. Such key cytokines include proinflammatory cytokines (tumour necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and interleukin-17 (IL-17)) and anti-inflammatory cytokines (mainly IL-10).…”
Section: Introductionmentioning
confidence: 99%